Ayat al-qur’an beserta hadist moderat dalam beragama - Nabila, Syahda (Maliki Interdisciplinary Journal, 2025)
Moderation in religion is an approach that emphasises a balance between spiritual beliefs, interfaith tolerance, and adaptation to social dynamics. This concept aims to avoid extremism, both in the form of radicalism and excessive liberalism, by promoting the values of justice, wisdom, and respect for diversity. In the context of a multicultural society, religious moderation plays an important role in creating social harmony, strengthening unity, and overcoming potential conflicts that arise from different beliefs. This article explores the principles of moderation, challenges in its implementation, and strategies to strengthen understanding and practice of religious moderation. This approach is expected to be the foundation for building an inclusive, peaceful and civilised society. This article aims to further analyse the Qur'anic verses and hadith on religious moderation. The research method used is qualitative research with the type of literature study or library research. This library study is conducted by accessing various references such as scientific journals, books, and articles related to the verses of the Qur'an and hadith in religious moderation.